2021
DOI: 10.1063/5.0067231
|View full text |Cite
|
Sign up to set email alerts
|

Orientation and actual growth mechanism of ZnO nanorods through hydrothermal method on gold seed layer

Abstract: In this study, the hydrothermal method was employed to synthesize an oriented ZnO nanorod array on an annealed gold seed layer coated on a glass substrate from different precursor concentrations. Zinc nitrate hexahydrate and hexamethylenetetramine were used as starting materials for ZnO nanorod growth. The effect of gold seed layer roughness on the orientation of ZnO nanorods is presented. The morphology of the nanorods shows that oriented ZnO nanorods were obtained after deposition on the annealed gold seed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…ZnO nanorods produced on both annealed and un annealed Cr/Au seed layer present a completely different morphology as discussed by Mustafa et al [25] and Younas et al [26]. The nanorods produced on annealed Cr/Au seed layer has better orientation then the nanorods produced on un annealed seed layer with same precursors concentration as shown in Figures 3 and 4.…”
Section: Zno Nanorods Growthmentioning
confidence: 68%
See 1 more Smart Citation
“…ZnO nanorods produced on both annealed and un annealed Cr/Au seed layer present a completely different morphology as discussed by Mustafa et al [25] and Younas et al [26]. The nanorods produced on annealed Cr/Au seed layer has better orientation then the nanorods produced on un annealed seed layer with same precursors concentration as shown in Figures 3 and 4.…”
Section: Zno Nanorods Growthmentioning
confidence: 68%
“…The initial growth of the nanorods is started on the grains produced on the annealed substrate, and further growth is proceeded by the heterogeneous nucleation in the solution. It's also possible that some of the nanorods growth took place in the fluid through homogenous nucleation, and then fall down on the seed layered substrate [26]. The increase of the nucleation sites on the annealed seed layer improves the alignment and orientation of the nanorods.…”
Section: Internal Mechanism Of Zno Nanorods Growth and Orientationmentioning
confidence: 99%
“…Despite this effort, there still seems to be little agreement on which growth parameters are principally responsible for determining the spatial dimensions of the ZnO NRs. While some papers report that increasing the growth time results in longer and thicker hexagonal ZnO NRs [20,[26][27][28], others conversely observed that only the NR length increased without either a diameter change [29] or a modification in morphology [30]. Similar controversy in the literature exists about the use of the growth temperature to tune diameter and/or length of NRs.…”
Section: Introductionmentioning
confidence: 99%